2020
DOI: 10.3390/ijerph17217994
|View full text |Cite
|
Sign up to set email alerts
|

Community Based Interventions for Problematic Substance Use in Later Life: A Systematic Review of Evaluated Studies and Their Outcomes

Abstract: Problematic substance use (PSU) in later life is a growing global problem of significant concern in tandem with a rapidly ageing global population. Prevention and interventions specifically designed for older people are not common, and those designed for mixed-age groups may fail to address the unique and sometimes complex needs of ageing communities. We report findings from a systematic review of the empirical evidence from studies which formally evaluated interventions used with older people and reported the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Community‐based programs or spirituality/religion‐based programs ideally cover prevention, harm reduction, treatment, and aftercare for the AFM and ISUD. Literatures support the positive impact of community‐based treatment (Hafford‐Letchfield et al, 2020; Jiwa et al, 2008) and spirituality and faith (Grim & Grim, 2019; Walton‐Moss et al, 2013). Grim and Grim (2019) reported that interestingly, many behavioral health substance abuse treatment services in the US include a spirituality‐based element as embodied in the 12‐step programs and fellowships, the majority of which emphasize reliance on God or a Higher Power to stay sober.…”
Section: Discussionmentioning
confidence: 99%
“…Community‐based programs or spirituality/religion‐based programs ideally cover prevention, harm reduction, treatment, and aftercare for the AFM and ISUD. Literatures support the positive impact of community‐based treatment (Hafford‐Letchfield et al, 2020; Jiwa et al, 2008) and spirituality and faith (Grim & Grim, 2019; Walton‐Moss et al, 2013). Grim and Grim (2019) reported that interestingly, many behavioral health substance abuse treatment services in the US include a spirituality‐based element as embodied in the 12‐step programs and fellowships, the majority of which emphasize reliance on God or a Higher Power to stay sober.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, higher education levels and lower monthly incomes were correlated with less severe anxiety among these patients, likely influenced by their awareness of the disease and their financial situation (Gase et al, 2017;Knifton and Inglis, 2020). Additionally, the frequency of alcohol consumption was observed to have varying impacts on physical and psychological well-being (Hafford-Letchfield et al, 2020). An increased frequency of interventions leads to significantly greater physical stress and fatigue, subsequently elevating the sense of anxiety related to feelings of meaninglessness among elderly patients with senile cataracts (Song et al, 2022).…”
Section: Sexmentioning
confidence: 98%
“…The remaining drew on behavioral, narrative, and integrated or multidisciplinary approaches, which aimed to meet older people's needs holistically. [ 89 , 90 , 91 ] Interventions need to align with other areas of health and well-being and should be delivered in locations where older people normally seek or receive help.…”
Section: Preventive Interventions For Sudmentioning
confidence: 99%